2005
DOI: 10.1093/carcin/bgi150
|View full text |Cite
|
Sign up to set email alerts
|

Life-span inhalation exposure to mainstream cigarette smoke induces lung cancer in B6C3F1 mice through genetic and epigenetic pathways

Abstract: Although cigarette smoke has been epidemiologically associated with lung cancer in humans for many years, animal models of cigarette smoke-induced lung cancer have been lacking. This study demonstrated that life time whole body exposures of female B6C3F1 mice to mainstream cigarette smoke at 250 mg total particulate matter/m(3) for 6 h per day, 5 days a week induces marked increases in the incidence of focal alveolar hyperplasias, pulmonary adenomas, papillomas and adenocarcinomas. Cigarette smoke-exposed mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 47 publications
(70 reference statements)
1
76
1
Order By: Relevance
“…The etiology for lung cancer in the never-smoker may be due to in part to exposure to environmental tobacco smoke and other environmental and occupational carcinogens (e.g., radon). Although these exposures cannot account for spontaneous tumors in the mouse lung, it is interesting that these tumors develop in part through inactivation of genes, such as ER-a, DAPK, RAR-h, and H-cadherin, which are also silenced in adenocarcinomas from the never-smoker (9,20,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiology for lung cancer in the never-smoker may be due to in part to exposure to environmental tobacco smoke and other environmental and occupational carcinogens (e.g., radon). Although these exposures cannot account for spontaneous tumors in the mouse lung, it is interesting that these tumors develop in part through inactivation of genes, such as ER-a, DAPK, RAR-h, and H-cadherin, which are also silenced in adenocarcinomas from the never-smoker (9,20,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Female B6C3F1 mice (6-7 weeks old) were exposed to mainstream cigarette smoke for up to 30 months. Details of the exposure system have been described (9). Briefly, two 70-cm 2 puffs/min from research cigarettes (type 2R1, Tobacco Health Research Institute, Lexington, KY) were generated by smoking machines (type 1300, AMESA Electronics, Geneva, Switzerland).…”
Section: Tumor Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixtures, such as d ie s e l e m i s s i on s a nd t ob a c c o s m ok e , h a v e b e e n epidemiologically shown to have carcinogenic potential, but because of the difficulty of establishing appropriate methods to represent the human exposure situation, ie., inhalation through the respiratory tract, no experimental proof of lung carcinogenicity of tobacco smoke in animals has been obtained although carcinogenicity of individual components such as benz[a]pyrene, cadmium, 2-naphthylamine and nitrosamines have been individually confirmed by administration intratracheally, orally or subcutaneously. Hutt et al reported in 2005 the first study to demonstrate a robust increase in lung cancer in mice after a lifetime of inhalation exposure to a mainstream of cigarette smoke 27 . Their report clearly demonstrated that an airborne complex mixture to which human beings are exposed through the respiratory tract can be properly studied in experimental animals even though there are some limitations 28 .…”
Section: Discussionmentioning
confidence: 99%
“…NNK is a key ingredient of tobacco smoke carcinogens. It is reported that NNK exposure can induce promoter hypermethylation of several tumor suppressor genes (TSGs) in lung and liver carcinomas, such as cyclin-dependent kinase inhibitor 2A and RARβ (Pulling et al, 2001;Hutt et al, 2005). Lin et al (2010) reported that NNK can induce TSGs promoter hypermethylation through the accumulation of DNMT1 in mice and human lung cancer.…”
Section: -(Methylnitrosamino)-1-(3-pyridyl)-1-butanone Induces Retinmentioning
confidence: 99%